An Old Friend in a New Light: The Role of Osteocalcin in Energy Metabolism. Issue 2 (5th October 2011) - Sullivan, Tim R.; Duque, Gustavo; Keech, Anthony C.; Herrmann, Markus
SUMMARY: Accumulating evidence suggests interactions between bone and energy metabolism, which may affect the risk of cardiovascular disease. Recent animal studies indicate that osteocalcin (OC) plays a key role in the coordinated regulation of glucose and insulin metabolism while insulin receptors on osteoblasts may regulate bone turnover and circulating OC levels. Association studies, weight loss interventions, and observational data lend some support to the existence and relevance of these mechanisms in humans. However, corroborating evidence from pharmacologic interventions in either bone or glucose metabolism is limited by the number, design, and complex pharmacological effects of the drugs used. Furthermore, such clinical trials are complicated by the alteration of metabolic feedback mechanisms in the insulin resistant state. Purpose‐designed studies are needed to further establish the existence and significance of the role of OC and its subfractions in human insulin metabolism. In this review we summarize existing animal evidence regarding the role of OC and its subfractions in bone and energy metabolism and assess current clinical trial evidence relating to the significance and consequences of this relationship in humans.